Nature Reappraisers, Benefits for the Environment: A Model Linking Cognitive Reappraisal, the “Being Away” Dimension of Restorativeness and Eco-Friendly Behavior - Panno, Angelo; Theodorou, Annalisa; Carrus, Giuseppe; Imperatori, Claudio; Spano, Giuseppina; Sanesi, Giovanni (Frontiers in Psychology, 2020)
In the last decades, an increasingly prominent role has been given to the motivational factors that can promote pro-environmental behavior. In this contribution, we focus on the role of the individual’s ability to shape the emotions originating from nature in engaging in pro-environmental behavior. In particular, we expect that an emotion regulation strategy as cognitive reappraisal should positively predict pro-environmental behavior, through enhanced perceived restorativeness attributed to the natural environment in terms of the experience of “being away”. One-hundred and fifteen visitors to an urban park (Parco Nord Milano) filled out a questionnaire including measures of cognitive reappraisal, the experience of “being away”, and pro-environmental behavior while in the park. Results confirmed that cognitive reappraisal was positively and significantly related to pro-environmental behavior. Importantly, the indirect effect of cognitive reappraisal on pro-environmental behavior through the experience of “being away” was significant. Findings suggest the importance of implementing interventions aimed at promoting the habitual use of cognitive reappraisal to enhance the experience of “being away” and, thus, sustain pro-environmental behavior.